Low-cost potting mix for quality seedling production of multipurpose calliandra (Calliandra calothyrsus) in humid tropics of Kerala - Raj, A.K.; Kunhamu, T.K.; Kiroshima, S. (Indian Journal of Agroforestry, 2020)
Availability of quality planting stock at cheaper rates is a prerequisite for promoting agroforestry models in farmer’s field. Potting media used in nursery has profound influence on seedling quality and cost. Commonly used potting materials, sand and FYM have become scarce and costly in recent years demanding cheaper and viable alternatives. Here, the feasibility of using coir pith compost (CC) and vermincompost (VC) as potting materials for the production of a prominent agroforestry species calliandra in nurseries was investigated through the study of their different proportions with soil (1:1, 2:1, 2:1:1, 3:1:1 and 4:1:1 ) on target plant growth, in comparison with the conventional medium of soil, sand, FYM in 2:1:1 ratio. Seedling growth parameters after three months and their field evaluation for six months revealed the highest shoot length, leaf and branch number, collar diameter and dry matter production in soil, VC, CC, 2:1:1 media as compared to other treatments, with a reduction in production cost by 40% than the conventional one. Even their wider ratios (3:1:1 and 4:1:1) performed better as compared to the conventional mixture. However, the replacement of sand and FYM by either VC or CC alone adversely affected seedling growth indicating the equal requirement of the above two composts to optimize the physico-chemical properties and nutrient content of the media for maximum growth. The study thus, recommends soil, coir pith compost and vermicompost in 2:1:1 ratio as a cheaper potting mix for production of quality calliandra seedlings, in areas where organic wastes and coir pith are readily available.